PENGARUH MODEL PROBLEM BASED INSTRUCTION TERHADAP KETERAMPILAN PROSES SAINS DAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPA DI SMP - Maya Sinta Ayu Septriningsih; Singgih Bektiarso; Trapsilo Prihandono (JURNAL PEMBELAJARAN FISIKA, 2017)
This study focused on influence of Problem Based Instruction Model in science learning at SMP. The purposes of this research were: (1) to describe student’s science process skills in physics during learning process, (2) there was a significant difference on the learning outcomes of students who were given a Problem Based Instruction Model and were not given the Problem Based Instruction Model. This research was experimental study with posttest only control group design. The population in this study was VIII class and the sample were 8.1 and 8.2 class of SMP 1 Probolinggo. The data were collected by interview, observation, documentation, portfolio, and test. Data analysis techniques were descriptive, percentage, and T-Test using SPSS 22. The results of this research were the average of student’s science process skills was 3,44 (good criteria) and the significant difference on the learning outcomes of student was 0,000 using T-Test SPSS 22. This research can be concluded: first, the average of student’s science process skills is in good criteria. Secondly, there is a significant difference in the learning outcomes of students who use Problem Based Instruction Model and who do not use Problem Based Instruction Model. Keywords: Problem Based Instruction Model, Student’s Science Process Skills, Learning Outcomes.